Mathematical Critical Thinking Ability in Solving HOTS Problems Based on Cognitive Style and Gender - Widyastuti, Erna; Jusra, Hella (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aims to identify students’ mathematical critical thinking ability in solving HOTS problems based on cognitive styles and gender. It is a descriptive and qualitative study. It used the purposive sampling technique to determine 4 subjects based on the categories of impulsive and reflective cognitive styles covering both male and female students. Data were collected by interviews, documentation, the MFFT test, and the mathematical critical thinking skill test using HOTS questions. The results showed that students who have the impulsive cognitive style could meet the FRISCO indicators in solving HOTS questions. Students with a reflective cognitive style could not meet the indicator of reason as they were unable to provide supporting reasons related to the information found. Female students provided a more detailed, coherent, and clearer explanation in solving HOTS questions compared to male students.